2021
DOI: 10.3390/biomedicines9070789
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation with Mild Stimulation Intensity Exerts Anti-Inflammatory and Neuroprotective Effects in Parkinson’s Disease Model Rats

Abstract: Background: The major surgical treatment for Parkinson’s disease (PD) is deep brain stimulation (DBS), but a less invasive treatment is desired. Vagus nerve stimulation (VNS) is a relatively safe treatment without cerebral invasiveness. In this study, we developed a wireless controllable electrical stimulator to examine the efficacy of VNS on PD model rats. Methods: Adult female Sprague-Dawley rats underwent placement of a cuff-type electrode and stimulator on the vagus nerve. Following which, 6-hydroxydopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Via an inflammatory reflex of the CAP, the vagus nerve perceives the peripheral inflammatory signal and then releases the neurotransmitter acetylcholine (Ach), which stimulates alpha 7 nicotinic acetylcholine receptor (α7nAchR) in multiple immune cells such as macrophage, and eventually inhibits the production of pro-inflammatory cytokines and cytokine-related devastating effects [ 6 , 7 , 8 ]. It has been widely studied that the activation of CAP, through stimulating the vagus nerve or activating α7nAchR receptor by a specific cholinergic agonist can effectively attenuate the development of various inflammatory diseases, including endotoxemia, rheumatoid arthritis, ischemia/reperfusion injury, and hemorrhagic shock [ 9 , 10 , 11 , 12 , 13 , 14 ]. Recent studies indicate that CAP may also play a functional role in the regulation of cardiovascular diseases such as atherosclerosis (AS), a chronic inflammatory condition [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Via an inflammatory reflex of the CAP, the vagus nerve perceives the peripheral inflammatory signal and then releases the neurotransmitter acetylcholine (Ach), which stimulates alpha 7 nicotinic acetylcholine receptor (α7nAchR) in multiple immune cells such as macrophage, and eventually inhibits the production of pro-inflammatory cytokines and cytokine-related devastating effects [ 6 , 7 , 8 ]. It has been widely studied that the activation of CAP, through stimulating the vagus nerve or activating α7nAchR receptor by a specific cholinergic agonist can effectively attenuate the development of various inflammatory diseases, including endotoxemia, rheumatoid arthritis, ischemia/reperfusion injury, and hemorrhagic shock [ 9 , 10 , 11 , 12 , 13 , 14 ]. Recent studies indicate that CAP may also play a functional role in the regulation of cardiovascular diseases such as atherosclerosis (AS), a chronic inflammatory condition [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intensities of 0.25-0.5 mA improved movement impairment and reduced astrocyte and microglia activation. Intensities of 0.1 and 1 mA showed no improvement [114]. In both cases, the authors attribute an anti-inflammatory and neuroprotective effect to VNS.…”
Section: Parkinson's Diseasementioning
confidence: 78%
“…The resultant image block was 72 μm in voxel resolution (isotropic). Each scan spanned 1.8 cm of nerve length, with 0.3 cm overlap (i.e., 16.67%) between adjacent blocks to serve image reconstruction.…”
Section: Microct and Image Sub-volume Reconstructionmentioning
confidence: 99%
“…presents the opportunity to modify function both within the brain and the majority of organs within the viscera. [12][13][14][15][16][17][18][19][20][21] Several recent studies in animal models have suggested that smaller, multi-contact electrodes may more selectively stimulate specific portions of the cervical vagus to take advantage of underlying functional organization to better isolate intended activation of therapeutic fibers from unwanted activation of off-target fibers. 22,23 The activation of lowthreshold large-diameter motor efferent fibers of the vagus that innervate the deep muscle of the necks putatively drives the most common side effects, causing cough, throat pain, voice alteration, and dyspnea reported in up to 66% of patients.…”
mentioning
confidence: 99%